Treatment of duodenal obstruction by gallstone - Asiner, Boris; Praderi, Raul (Cirugía del Uruguay, 1971)
The analysis of surgical tactics in two cases of duodenal obstruction due to gallstones includes: -the obstructive problem: duodenal obstruction due to gallstones; -biliodigestive cholecystoduodenal fistula, biliary disease; and -problems connected with closure and management of sutured dundenum. There is a tendency to solve and biliary problems in one adding simple procedures for "discharge". Both cases were successfully solved. In one case urgent consultation was held due to high digestive hemorrhage. In the other there was an obstructive jaundice due to angiocolitis. These complications were also treated.